Case Report: Superior Mesenteric Artery Syndrome in an Adolescent With Cannabinoid Hyperemesis - Berken, Jonathan A.; Saul, Samantha; Osgood, Peter T. (Frontiers in Pediatrics, 2022)
Background Superior mesenteric artery syndrome (SMAS) occurs when the third portion of the duodenum is compressed between the superior mesenteric artery (SMA) and the aorta, causing duodenal obstruction. This condition most commonly arises from marked weight loss that reduces the size of the fat pad between these vessels, causing greater acuity of angulation. We present an unusual case of SMAS occurring in an adolescent due to precipitous weight loss resulting from cannabinoid hyperemesis syndrome (CHS). Case Presentation A 17-year-old adolescent presented emergently with voluminous bilious emesis. She endorsed a history of recent weight loss and a longstanding history of chronic heavy cannabis use associated with recurrent nausea and vomiting. Her chronic symptoms satisfied the Rome IV criteria for cannabinoid hyperemesis syndrome, but her acute vomiting symptoms were more extreme. Evaluation was significant for mild abdominal tenderness and fullness of the epigastrium. Contrast abdominal CT demonstrated moderate gastric and proximal duodenal distention with tapering of the lumen between the SMA and the aorta, consistent with SMAS. Conclusions To our knowledge, this is the first reported case of SMAS occurring as the result of CHS. Clinicians should be aware of this possible juxtaposition, when a patient with a history of chronic excessive cannabis use, stereotypical vomiting resembling cyclic vomiting syndrome, and considerable rapid weight loss presents with a sudden exacerbation of symptoms, even when a normal BMI is maintained.